Pre‐prostatectomy membranous urethral length as a predictive factor of post prostatectomy incontinence requiring surgical intervention with an artificial urinary sphincter or a male sling. Issue 4 (9th March 2022) - Oza, Priyanka; Walker, Nicholas Faure; Rottenberg, Giles; MacAskill, Findlay; Malde, Sachin; Taylor, Claire; Sahai, Arun
Abstract: Aims: To ascertain whether the membranous urethral length (MUL) is predictive of postprostatectomy incontinence (PPI) that requires surgery such as artificial urinary sphincter (AUS) or male sling (MS). Methods: Men who had undergone AUS or MS for PPI were identified from a prospectively maintained database and compared to a control group of men who were continent at 12 months after radical prostatectomy. MUL in sagittal and coronal planes, sphincter height and width were measured on prebiopsy T2‐weighted MRI scans. Sphincter volume was estimated as an ellipsoid cylinder. Results: A total of 95 patients (64 AUS and 31 MS) were compared to 60 continent controls. There was no statistical difference in presenting PSA, prostate volume, and T‐stage. The mean MUL in sagittal and coronal planes was 11.31 mm ( SD : 2.6, range: 6–17 mm) and 11.43 mm ( SD : 2.94, range: 5–17 mm) in patients who had AUS and MS, respectively; 15.23 mm ( SD : 4.2, range: 8.25–25 mm) and 15.75 mm ( SD : 4.1, range: 8–24 mm) in controls ( p < 0.01). No men in the PPI surgery group had an MUL >17 mm compared to 35% (20/57 sagittal, 20/58 coronal) of controls. The odds ratio for requiring surgery for PPI was 13.4 for sagittal MUL <9 mm and 3.2 if the MUL <12 mm. Conclusions: Patients who had surgery for PPI had a significantly shorter MUL and sphincter volume than continent controls. Men with an MUL >17 mm are unlikely to require surgery for PPI whereas an MUL <12 mm significantly increases the risk of requiring surgery for PPI. MUL should be considered when discussing treatment options for prostate cancer.